(untitled) (UKLO Proceedings, 2025)
Introduction: Air pollution is a growing concern due to its adverse effects on health, particularly respiratory conditions such as allergic reactions of the upper respiratory tract. This study investigates the relationshipbetween air pollution exposure and thefrequency and severity of allergicsymptoms in individuals from differentdemographic backgrounds. Materials and Methods: A questionnaire-based study will be conducted among individuals of varying ages, occupations, and living conditions. The survey will include questions about personal exposure to outdoor and indoor air pollution, the frequency of allergic symptoms, and the perceived quality of air in the participant’s environment. Participants will also be asked to assess any correlation between air pollution and their allergic symptoms, including sneezing, nasal congestion, throat irritation, and eye itching. Discussion: Preliminary data suggest a strong correlation between exposure to both outdoor and indoor air pollution and the frequency of allergic reactions, particularly during high-pollution seasons like spring and autumn. Many participants reported worsening symptoms in polluted environments and improvement in cleaner air settings, highlighting the role of air quality in managing allergic conditions. Conclusion: The study confirms that air pollution significantly affects allergic reactions in the upper respiratory tract. Measures such as improving air quality and reducing exposure to pollutants, especially in urban and industrial areas, are essential for managing respiratory allergies. Further research is needed to explore long-term effects and interventions to mitigate the impact of air pollution on respiratory health.